Experiential learning : a practical guide for training, coaching and education - Beard, Colin (Colin M.); Wilson, John P. (John Peter), 1955 August 11- (London ; New York : Kogan Page, 2018)
In a fast-paced and innovative world, traditional training methods can no longer be relied on to improve performance and engagement, or promote behavioural change. Experience-based learning, in which the experience is central to the learning process, is more affordable, appealing and effective than ever before. Experiential Learning combines in-depth theory with international case studies from companies including KidZania, Shell and the UK National Health Service (NHS) and provides numerous practical tools for developing and delivering learning experiences in both for-profit and not-for-profit organizations. It presents a simple model, the Learning Combination Lock, which enables trainers, coaches, facilitators and educators to select the best strategies for their circumstances to maximize comprehension, knowledge retention and application. Essential reading for anyone designing and delivering learning experiences, this book covers areas such as experiential learning activities, indoor and outdoor learning environments, creative learning, working with the senses and emotions to help promote learning, and reviewing and evaluating initiatives. In addition to featuring new case studies and examples, this updated fourth edition brings a holistic understanding of human learning to mindfulness and well being, experience and language, and digital games in the design of multisensory experiences. Online supporting resources consist of audio files exploring sensory intelligence--back cover.
01. A brief introduction to experiential learning -- Part One. Experiential learning: foundations and fundamentals : 02. Practical answers to some theoretical questions -- 03. Designing, delivering and evaluating experiential learning -- Part Two. The Learning Combination Lock model : 04. The outer-world learning environment: other humans, other living creatures, and spaces and places (the belonging dimension) -- 05. Experiential learning activities, behaviours and actions (the doing dimension) -- 06. Sensory experience and sensory intelligence (SI) (the sensing dimension) -- 07. Experience and emotions (the feeling dimension) -- 08. Experience, knowing and intelligence (the knowing dimension) -- 09. Deeper learning (the being dimension) -- Part Three. Experiential learning and the future : 10. Imagining, experiencing and learning from the future.
Includes bibliographical references (pages 329-350) and index.
Keywords: Experiential learning -- Handbooks, manuals, etc; Active learning -- Handbooks, manuals, etc; Employees -- Training of -- Handbooks, manuals, etc; Active learning; Employees -- Training of; Experiential learning; Handbooks and manuals